METHODS OF ASSESSING KNOWLEDGE OF THE RUSSIAN LANGUAGE IN PUPILS OF SCHOOLS WITH UZBEK LANGUAGE OF INSTRUCTION - Касымова Ф. С. (Web of Journals Publishing, 2024)
The article mentions the use of new pedagogical technologies in Russian language lessons in secondary schools, namely the role of assessment sheets in determining the reader's knowledge.
Keywords: assessment sheet, form of control, motivation, differentiated assessment, critical thinking.